Technology, organizational and environmental (TOE) factors influencing enterprise application integration (EAI) implementation in Omani Government Organizations - Al Balushi, Fatma Mohammed Abdullah (Indian Society for Education and Environment, 2016)
Objective: This paper presents the primary study findings about the factors that influence Enterprise Application Integration (EAI) implementation in Omani Government Organizations. The case study selected has been implementing EAI technology between three government organizations. Method: The case study analysis aimed to investigate the essential factors based on Technology, Organizational and Environmental (TOE) model. Also, this study employs Grounded Theory Approach (GTA) and Lewin’s change model. Findings: As a result of this primary case study, there are 8 factors found to be influential during the implementation process. Application: a framework has been proposed from the findings to provide a guideline for practitioners in Omani government organizations for the newer EAI implementation projects.